2017
DOI: 10.1097/md.0000000000005842
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of chloral hydrate for conscious sedation of infants in the pediatric cardiovascular intensive care unit

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The main reason was that there was no drug-related vomiting in the rectal CH group. According to the literature, one of the most commonly reported adverse effects of oral CH is vomiting, [ 12 , 21 ] and its incidence varies from 0.53% to 11.5%. [ 22 , 23 ] In the rectal CH group, none of the children experienced drug-related vomiting, thus, rectal administration could avoid vomiting caused by oral administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main reason was that there was no drug-related vomiting in the rectal CH group. According to the literature, one of the most commonly reported adverse effects of oral CH is vomiting, [ 12 , 21 ] and its incidence varies from 0.53% to 11.5%. [ 22 , 23 ] In the rectal CH group, none of the children experienced drug-related vomiting, thus, rectal administration could avoid vomiting caused by oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 26 ] In fact, CH has been used in infants with congenital heart disease with/without pulmonary infection in the pediatric cardiovascular intensive care unit. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing lung function or structure in the very early CF years (0–5 years) is challenging, as infants are unable to consciously perform a co-ordinated effort such as spirometry. Infants and, in some instances pre-schoolers, may need to be sedated for lung function testing or imaging which presents several ethical and practical considerations [ 51 , 52 ]. In children with minimal disease, it may take years to detect a signal showing that an intervention alters the outcome.…”
Section: How To Involve Children In Researchmentioning
confidence: 99%
“…If sedation fails due to a prolonged time to reach sedation or side effects, the hospitalization of pediatric patients may be extended, causing significant setbacks to the diagnosis and treatment plans [9].Chloral hydrate is the most commonly used drug for pediatric sedation, with a rapid onset of action and recovery [3,9]. In clinical practice, chloral hydrate at a dose of 50 to 75 mg/kg is administered orally to infants and can be administered once again at a dose less than the initial maximum dose after 20 to 30 minutes according to the criteria recommended in the guidelines for pediatric sedation compiled by the Korean Society of Pediatric Anesthesiologists [9,10].Previous studies have shown that sedation using chloral hydrate is affected by several variables, including dosage, the administration method, weight, sex, compliance, the duration and nature of treatment, and the patient's health status [11,12]. In particular, sedation failure is frequent in clinical practice when chloral hydrate is administered at the manufacturer's…”
mentioning
confidence: 99%